2020
DOI: 10.3390/jcm9041013
|View full text |Cite
|
Sign up to set email alerts
|

Late Evening Snack with Branched-Chain Amino Acids Supplementation Improves Survival in Patients with Cirrhosis

Abstract: The clinical efficacy of a late evening snack (LES) is well documented in patients with cirrhosis, but its effect on survival remains unclear. This cohort study aimed to compare the overall survival between LES-treated patients and untreated patients. We conducted a retrospective cohort study to determine the effect of LES, which is defined as an oral intake of a branched-chain amino acids (BCAA)-enriched nutrient before bedtime, on survival in 523 patients with cirrhosis seen at a tertiary referral center in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…We excluded six out of these articles with reasons as follows: (1) no clear BCAA group (33,34), (2) abstract without full text ( 35), (3) involving hepatocellular carcinoma (HCC) patients ( 36), ( 4) not involving cirrhosis patients (37), and ( 5) outcome influenced selection (38). Accordingly, the qualitative synthesis included 11 articles, out of which five were included in the quantitative synthesis (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Summary Measures and Synthesis Of Resultsmentioning
confidence: 99%
“…We excluded six out of these articles with reasons as follows: (1) no clear BCAA group (33,34), (2) abstract without full text ( 35), (3) involving hepatocellular carcinoma (HCC) patients ( 36), ( 4) not involving cirrhosis patients (37), and ( 5) outcome influenced selection (38). Accordingly, the qualitative synthesis included 11 articles, out of which five were included in the quantitative synthesis (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Summary Measures and Synthesis Of Resultsmentioning
confidence: 99%
“…Routine physical activity or late evening snack alone leads to reversal of anabolic resistance, sarcopenia, and improvements in both survival and health-related quality of life parameters in patients with cirrhosis ( 30 , 33 , 59 ). It is, therefore, noteworthy that effects of AXA1665 were demonstrated in the context of SOC.…”
Section: Discussionmentioning
confidence: 99%
“…When combined with exercise, essential AAs have been shown to increase muscle mass in patients with cirrhosis ( 31 , 32 ). BCAA supplementation in these patients has also demonstrated stimulation of muscle protein synthesis and improved clinical outcomes ( 33 37 ). However, provision of BCAAs without additional proteogenic-stimulating essential AAs (eg, histidine, lysine, and threonine) could limit maximal anabolic response in severe catabolic states such as cirrhotic sarcopenia ( 12 , 38 , 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inverse probability of treatment weighting analysis also revealed that LES significantly improved the prognosis of patients with cirrhosis (HR, 0.57; 95% CI, 0.33-0.99). [ 19 ]…”
Section: Resultsmentioning
confidence: 99%